Investigation of Rheological and Physical Properties of SBS and WCO Composite Modified Bitumen - Cavdar, Erman; Kumandas, Aytug; Sahan, Neslihan; Kabadayi, Ersoy; Oruc, Seref (Turkish Chamber of Civil Engineers, 2024)
Nowadays, the use of waste materials in various industries is becoming widespread in order to promote waste recycling. Thus, scientists are researching the use of waste materials in bitumen modification. In this study, it was aimed to investigate the effect of waste cooking oil (WCO) on the physical and rheological properties of unaged Styrene-Butadiene-Styrene modified bitumen (SBSMB) by adding WCO at different ratios (1, 3, 5, 7, and 9%) to SBS modified bitumen. Accordingly, rotational viscosity (RV) tests and rheological tests with dynamic shear rheometer (DSR) based on the determination of complex shear modulus (|G*|) and phase angle (delta) were conducted along with the traditional bitumen tests. As a result of the experimental study, it was observed that adding WCO increased the workability and fatigue resistance of SBSMB, however, decreased its rutting resistance. Therefore, the mixing and compaction temperatures of SBSMB can be decreased by adding low amounts of WCO without excessive performance loss. Thus, during the construction of asphalt pavements, environmental damage can be reduced by utilizing waste materials and reducing CO2 emissions.
Çavdar, Erman/0000-0002-0238-5245; Kumandaş, Aytuğ/0000-0003-1765-9963
Keywords: Styrene-Butadiene-Styrene; Polymer Modified Bitumen; Waste Cooking Oil; Workability; Rheology